Indirect effect of patient outcome expectation on improvement through alliance quality: A meta-analysis. (18th August 2021) - Constantino, Michael J.; Coyne, Alice E.; Goodwin, Brien J.; Vîslă, Andreea; Flückiger, Christoph; Muir, Heather J.; Gaines, Averi N.
Abstract: Objective: A meta-analysis revealed a positive correlation between patients' optimistic baseline, or early treatment, outcome expectation (OE) and posttreatment improvement (Constantino, Vîslă, et al., [2018]. A meta-analysis of the association between patients' early treatment outcome expectation and their posttreatment outcomes. Psychotherapy, 55 (4), 473–485. https://doi.org/10.1037/pst0000169 ). However, little is known about mechanisms through which OE operates. Increasingly, several individual studies have pointed to higher therapeutic alliance quality as a promising mediator (candidate mechanism) of the positive OE-improvement link. In this study, we conducted the first meta-analysis of this indirect effect, hypothesizing that alliance would partially mediate the OE-outcome link. Method: We included published articles involving a clinical sample; therapist-led treatment of at least 3 sessions; pre- or early treatment patient OE measures; during-treatment patient-rated alliance measures; posttreatment outcome measures; and statistical tests of mediation. This meta-analysis included 10 independent samples and over 1, 000 patients. Results: As expected, better alliance quality partially mediated the association between more optimistic OE and improvement; that is, although both were significant, a multivariate analysis revealed that the direct effect was significantly lower than the total effect (standardized difference = −.12, p  < .001, 95% CI [−.20, −.05]). Publication bias was low, as was heterogeneity except for the alliance-outcome path. Conclusions: Better alliance may be one process that helps transmit the therapeutic influence of early patient OE.